Maximizing Terahertz Energy Absorption with MXene Absorber - Xinliang Li; Hao Luo (Nano-Micro Letters, 2023)
Highlights MXene film absorbers enable the near theoretical absorption strength in extremely wide wavebands of 0.5–10 THz.